PERLINDUNGAN HUKUM BAGI PEMBELI BERITIKAD BAIK TERHADAP KEPEMILIKAN SERTIFIKAT TANAH GANDA - Warni Purba; Asep Rachman Saputra; Elang Pratama Efendi; Agus Septima Ridwan (JOURNAL OF LAW AND NATION, 2026)
This study aims to analyze the legal gap in Article 19 of Law Number 5 of 1960 concerning the Basic Agrarian Principles that triggers overlapping land certificate disputes, while also evaluating the legal protection afforded to good faith buyers under Indonesian positive law. The central problem is that buyers who have transacted lawfully nevertheless lose legal certainty when their certificate turns out to overlap with another party's certificate due to weak administrative validation. This research employs a normative juridical method with statutory and conceptual approaches through a literature study of primary and secondary legal materials. The findings reveal that the negative publication system with positive tendencies positions the certificate merely as strong evidence rather than absolute proof, thus remaining vulnerable to lawsuits and cancellation through material proof. Legal protection for good faith buyers under positive law remains partial because the state has not provided an automatic restoration or compensation mechanism, leaving honest buyers burdened with the obligation to independently file an unlawful act claim to recover their losses.